Evaluating the Short Run and Long Run Impacts of Unconditional Cash Transfers on Food-Seeking Behaviour: New Insights from BISP, Pakistan (The Pakistan Development Review, 2025)
We examine the impact of the cash transfer programme on food-seeking behaviour among ultra-poor segments of society. Food-seeking behaviour includes per adult’s daily calorie intakes, food diversity, stable availability of food, and a composite index of food security. The empirical analysis is based on three rounds of panel household surveys (2011, 2013, and 2016) using the regression discontinuity design (RDD). The results have shown that BISP beneficiaries, relative to non-beneficiaries, have a higher level of calorie intakes. The cash transfer helps them diversify their food basket with stable food availability and improved food security level in both short and long-run periods. Moreover, BISP cash transfer increases access to quality food groups such as meat, fish, and fruits in the long run. These beneficial influences of the cash transfer reveal much stronger long-run impacts as compared to short-run effects. The findings of this paper provide helpful policy insights related to the importance of the cash transfer programme. The BISP cash transfer appears to be an effective social assistance programme that holds sustainable long-run effects on ensuring household food and dietary requirements through incomeand substitution effects.